The Strategy Used in Translating Speech into Subtitle (Case Study: @america Video) - Olivia Feren Rezza Merliani; Farida Agoes (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2022)
This article discusses the strategy used in translating and subtitling @america’s video entitled “Fireside Chat with Rebecca Hwang: Creating Impactful Business.” The video is a virtual discussion about business, women empowerment, leadership, and entrepreneurship with a total duration of one hour. This video’s source language (SL) is English, and the target language (TL) is Indonesian. This study aims to find the realization of domestication and foreignization strategies and the tendency of translation strategy in the chosen video’s subtitle. This study was conducted with a qualitative method using theories of translation techniques by Molina & Albir (2002), translation strategy by Venuti (2001), translation quality by Nababan et al. (2012), and subtitle guidelines by BBC. This study shows that the domestication strategy was applied using adaptation, established equivalence, and transposition, while the foreignization strategy was applied using borrowing, literal translation, and calque. Furthermore, this study indicates that the tendency of the strategy used in this subtitle is foreignization with 883 total lines of subtitle.